2009
DOI: 10.1029/2009ja014283
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structures of magnetic depression in the Earth's high‐altitude cusp: Cluster multipoint observations

Abstract: [1] Magnetic depression structures (magnetic holes) of short time duration from seconds to minutes have been studied using Cluster data in the high-latitude cusp. Our multispacecraft analysis revealed that the magnetic depressions are spatial structures traveling across the spacecraft, and this result was further strengthened by the calculation of the boundary normal directions and velocities using various methods. In this article, we show that multiple properties of the magnetic depressions are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 49 publications
1
63
0
1
Order By: Relevance
“…From the "interlaced" magnetic field profiles, we can tell that the magnetic hole is a spatial structure, rather than a temporal effect (e.g. Shi et al, 2009a). This can be confirmed by considering the angle between the normals of its two boundaries.…”
Section: Spatial Structuressupporting
confidence: 50%
See 1 more Smart Citation
“…From the "interlaced" magnetic field profiles, we can tell that the magnetic hole is a spatial structure, rather than a temporal effect (e.g. Shi et al, 2009a). This can be confirmed by considering the angle between the normals of its two boundaries.…”
Section: Spatial Structuressupporting
confidence: 50%
“…As ions can be heated in the perpendicular direction by the quasi-perpendicular bow shock , mirror mode structures are observed in the corresponding terrestrial magnetosheath (Kaufmann et al, 1970;Crooker et al, 1979;Tsurutani et al, 1982) and in the terrestrial cusp (Shi et al, 2009a). Observations and numerical simulations have shown that magnetic peaks are rarely seen in mirror stable plasma because of their rapid decay, but magnetic holes could survive in a mirror stable plasma.…”
Section: Introductionmentioning
confidence: 98%
“…S1c,d,g). In our previous studies 35,36 , we have reviewed a method on how to empirically distinguish the spatial 'pass through' effects from temporal 'enter/retreat' ones based on the temporal sequences of the four spacecraft. In summary, if we find 'interlaced' profiles of parameters observed by different spacecraft, it should be interpreted as a spatial 'pass through' structure.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, event selection was made according to the particle energy flux in the lobe: we require that the energy band between 700 ev and 2 keV, and at least one order of magnitude for all energy bands, contain a particle energy flux greater than 8 Â 10 4 keVs À 1 cm À 2 si À 1 keV À 1 . Based on these criteria, only events with magnetosheath or cusp-like 35,36 ions with energy around 1 keV were selected, and the upflowing ions with lower energy 29,34 from the ionosphere were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation